Human frontiers, environments, and disease : past patterns, uncertain futures - McMichael, A. J. (Anthony J.) (Cambridge ; New York : Cambridge University Press, 2001)
This compelling account charts the relentless trajectory of humankind across time and geography, and its changing survival patterns, from several million years ago when our ancient ancestors roamed the African Savannah to today's populous, industrialised, globalising world.
Disease patterns in human biohistory -- Human biology: the Pleistocene inheritance -- Adapting to diversity: climate, food and infection -- Infectious disease: humans and microbes coevolving -- The Third Horseman: food, farming and famines -- The industrial era: the Fifth Horseman? -- Longer lives and lower birth rates -- Modern affluence: lands of milk and honey -- Cities, social environments and synapses -- Global environmental change: overstepping limits -- Health and disease: an ecological perspective -- Footprints to the future: treading less heavily.
Includes bibliographical references (pages 366-401) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: World health; Diseases and history; Sustainable development; Climatic changes -- Health aspects; Human ecology; Social medicine; Ecology; Social ecology; Global Health; Social Medicine; Ecology; Social Environment; Santé mondiale; Maladies et histoire; Développement durable; Climat -- Changements -- Aspect sanitaire; Écologie humaine; Médecine sociale; Écologie.; Écologie sociale; sustainable development; human ecology; ecology; HEALTH & FITNESS -- Health Care Issues; MEDICAL -- Public Health; MEDICAL -- Health Policy; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Diseases; MEDICAL -- Health Care Delivery; Social medicine; Ecology; Climatic changes -- Health aspects; Diseases and history; Human ecology; Sustainable development; World health; Climatic changes